1985
DOI: 10.1677/joe.0.1060387
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a sensitive direct assay for melatonin for investigation of circadian rhythms in different species

Abstract: The role of melatonin in animals which do not show marked seasonal changes in reproduction is disputed, in part because of the wide variation in reported concentrations. One reason for this may be the difficulties associated with the measurements of low molar concentrations of melatonin and the presence of a wide variety of potentially cross-reacting substances. The availability of a high affinity antiserum has allowed an assay, with low cross-reactivity and good sensitivity, to be established for the direct m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(35 citation statements)
references
References 0 publications
2
33
0
Order By: Relevance
“…These findings are confirmed by results of this study, showing that both P 4 production and corpus luteum growth were impaired in pinealectomised ewes. This result may be explained taking into account that melatonin remarkably increases mRNA expression of the LHCGR (but not FSHR) in human granulosa-luteal cells (Woo et al 2001).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…These findings are confirmed by results of this study, showing that both P 4 production and corpus luteum growth were impaired in pinealectomised ewes. This result may be explained taking into account that melatonin remarkably increases mRNA expression of the LHCGR (but not FSHR) in human granulosa-luteal cells (Woo et al 2001).…”
Section: Discussionmentioning
confidence: 94%
“…A previous study reported that pinealectomised ewes can have a normal pregnancy and deliver a healthy newborn (Kennaway et al 1985). More recent studies suggest that melatonin have a role in the process of ovulation (Tamura et al 2009), considering the presence of both types of membrane melatonin receptors in granulosa cells and that melatonin can up-regulate LHCGR mRNA (Woo et al 2001). The LH is essential for the initiation of luteinisation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations